Визначення можливих відносин спадкування в моделях класів - Новікова, Наталія (Видавництво Львівської політехніки, 2020)
A mechanism is proposed for analyzing the class model to identify classes that can be included in the inheritance hierarchy, as descendants from a common ancestor. The analysis is based on a comparing class formation goals, class methods and attributes.
Keywords: модель класу; атрибут класу; метод класу; типи даних; варіанти використання